The effect of mindfulness‐based programs on cognitive performance across the lifespan: A systematic review and meta‐analysis: Prevention (nonpharmacological) / Cognitive interventions. (7th December 2020) - Whitfield, Tim; Barnhofer, Thorsten; Acabchuk, Rebecca; Cohen, Avi; Lee, Michael; Lutz, Antoine; Wirth, Miranka; Coll‐Padros, Nina; Arenaza‐Urquijo, Eider M; Dautricourt, Sophie; Moulinet, Inès; Touron, Edelweiss; et al.
Abstract: Background: The primary focus of mindfulness‐based program (MBP) research to date has been on mental health. More recently, attention has turned to putative effects on cognition. An evidence synthesis is required to answer the key question of 'Do MBPs confer cognitive benefit, and if so, for whom?' A particularly crucial distinction is whether benefits differ according to individuals' age. We undertook a systematic review and meta‐analysis of all relevant research across the adult lifespan. Method: This review was conducted according to PRISMA guidelines, registered on Prospero (#CRD42018100904), and conducted searches of 7 databases. Included studies must have used a group‐based MBP, randomized participants to conditions, and used objective cognitive outcome measures. Two independent researchers assessed studies against criteria, extracted data and rated study quality. Meta‐analyses used robust variance estimation to assess overall effects. Result: Forty‐six studies were included in the systematic review, and 38 contributed effect sizes for meta‐analysis (see figure). Across the studies included in the meta‐analysis, the cognitive domains most frequently assayed were executive function (66 outcomes) and attention (60 outcomes). All outcome measures were pooled for analysis. The studies of working‐age adults (18‐65 years old; k =28) included healthy, psychiatric and neurological samples ( k =16 passively controlled studies; k =12 actively controlled studies). Studies of older adults (>65 years old; k =10) included healthy persons, and patients with subjective and objective cognitive impairment ( k =7 passively controlled studies; k =3 actively controlled studies). When combining healthy and clinical studies of working‐age adults, meta‐analysis yielded a non‐significant pooled effect of MBP participation on cognitive performance compared to control conditions ( g =0.28, p =.14; see table). A significant pooled effect was observed for the studies featuring older adults ( g =0.27, p <.05; see table). Conclusion: The current review assessed the effects of MBPs relative to control conditions on cognitive performance in adults across the lifespan, and found evidence of a significant positive effect for older adults only. No evidence of a benefit for younger populations was identified. As research in this fast‐developing field continues, it will be possible to examine whether effects vary according to healthy or clinical status, and to establish whether specific cognitive domains are differentially impacted.